An introduction to macroeconomic models - Kogiku, K. C. (New York: McGraw-Hill, 1968)
This volume presents macroeconomic models of income determination and economic growth
Bibliography: p. [198]-205.
obn22/01/2019
Loans
Keywords: Economics; Macroeconomics